PEMANFAATAN LINGKUNGAN SOSIAL SEBAGAI MEDIA PEMBELAJARAN PENDIDIKAN KEWARGANEGARAAN - Murdiono, Mukhamad (MAJALAH ILMIAH PEMBELAJARAN, 2008)
Civic education is the subject that is very tight his connection with social problems. The problem that developed in the community when being brought to the classroom as the material instruction for the student, however difficult to be solved because abstract. Therefore the use of the media really is needed in civic education learning. The teacher can use the social environment as the media in civic education learning. Using the social environment as the media instruction will make the teaching and learning process more significant because the students are faced with the real fact and condition naturally. There are some advantages that were obtained from the activity studied the social environment in the teaching dan learning process, sttch as: the activity studied mort:? interesting and did not bore, learned to be more significant, materials that were studied more rich and factual, the learning activity more comprehensive and active, the studying source became richer, and the student more understood and experienced aspects of the available life fully in environment.